Usage de l’instruction au sosie pour la conception d’actions de formation en situation de travail (AFEST) : une illustration avec des liquidateurs/trices de retraite - Stéphane Balas; Solange Ciavaldini-Cartaut; Jean-François Métral (Éducation et Socialisation)
This article aims to gain a better understanding of the theoretical and methodological questions raised by AFEST systems. It presents a methodological approach based on instruction to the double as part of professional didactic engineering for AFESTs. On the basis of empirical material collected from pension liquidators, we are studying how the instruction to the double makes it possible to identify the learning situations for an AFEST but also how this approach can constitute a training device for the actors. Our results confirm the interest of such an approach on both counts. However, this work leads to recommend the construction of a more precise framework with the actors, oriented, from the start, towards the issues of AFEST. This reflection also leads us to recall that such a method, which makes it possible to identify the complexity of the activity of professionals, must be put at the service of an engineering which does not reduce this complexity.